ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PROFITABILITAS USAHA TERNAK AYAM POTONG TAMBUNAN DI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Welly Edward; Henny Indrawati; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this researh is to know and analyze the factors that influence the profit of Tambunan’s chicken livestock. The population in this study is mr. Tambunan and the sample in this study 32 periods of harvest by using saturated sample technique. Data analysis used multiple regresion analysis. The results showed that the cost, selling prie, and sales volume significantly influence the profit of poultry farm in sub districk of coastal city of pekanbaru, and profit in the period november – december amounted to Rp 13,270,000 with a percentage of 11,94 % higher than the interest rate of Bank Bri of 5.1 % which meansthe Tambunan venture profitable.Keywords: Profit, cost, selling price, and sales volume